2014
DOI: 10.1370/afm.1596
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Mild Cognitive Impairment in General Practice: Results of the German AgeCoDe Study

Abstract: PURPOSEThe concept of mild cognitive impairment (MCI) has recently been introduced into the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) as mild neurocognitive disorder, making it a formal diagnosis. We investigated the prognostic value of such a diagnosis and analyzed the determinants of the future course of MCI in the AgeCoDe study (German Study on Ageing, Cognition, and Dementia in Primary Care Patients). METHODSWe recruited 357 patients with MCI aged 75 years or older from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 34 publications
(52 reference statements)
2
43
1
10
Order By: Relevance
“…Yet, more than half the DSM5‐MCI cases ( n = 78, 56.1%) were alive and non‐demented 4.5 years after the baseline assessment. Even in a clinical setting, in primary care, using diagnostic criteria ‘very similar to the mild neurocognitive disorder in the DSM‐5' the German AgeCoDe study found that only one‐quarter of patients with MCI have progression to dementia within the next 3 years . Therefore, these results suggest that there is still some way to go for recommending the MCI concept for wider use in population‐based settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, more than half the DSM5‐MCI cases ( n = 78, 56.1%) were alive and non‐demented 4.5 years after the baseline assessment. Even in a clinical setting, in primary care, using diagnostic criteria ‘very similar to the mild neurocognitive disorder in the DSM‐5' the German AgeCoDe study found that only one‐quarter of patients with MCI have progression to dementia within the next 3 years . Therefore, these results suggest that there is still some way to go for recommending the MCI concept for wider use in population‐based settings.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this study shows that using more stringent DSM5‐MCI criteria is associated with an increased rate of conversion to dementia and AD, regardless of how progression to dementia is measured, when compared with the more classical P‐MCI criteria . Still, most MCI individuals do not develop dementia, and both clinicians and health administrators should be cautious when transferring the concept of MCI into population‐based settings as this might create unnecessary concern . Incorporation of genetic and biomarker assessments in future studies, in addition to the clinical assessment of MCI, may lend added clarity in the crucial search of early identifiers of individuals at risk of dementia and AD.…”
Section: Discussionmentioning
confidence: 99%
“…In a large prospective cohort study of patients with MCI, overall, 41.5% of the patients had remission of symptoms with normal cognitive function 1.5 and 3 years later, 21.3% showed a fluctuating course, 14.8% had stable symptoms and 22.4% had progression to dementia 47. However, even in individuals who convert to normal cognition after a diagnosis of MCI, the risk of developing dementia later in life remains high in this population 48.…”
Section: Definitions and Diagnostic Criteriamentioning
confidence: 99%
“…Die biomarkerorientierte Demenzdiagnostik hat dazu geführt, dass die Wahrscheinlichkeit einer korrekten Diagnosestellung der Alzheimer-Krankheit bereits im Stadium der leichten kognitiven Störung (MCI) möglich ist [1,2]. Die Progression von einer leich-ten kognitiven Störung zu einer Demenz ist gegenwärtig vor allem im Forschungszusammenhang von Interesse [3]. Hausärzten wird eine Schlüsselrolle bei der frühzeitigen Differenzialdiagnostik kognitiver Störungen zugeschrieben [4,5].…”
Section: Introductionunclassified